Electrospun polyimide-based thin-film composite membranes for organic solvent nanofiltration - You, Xiaofei (2022)
Electrospun polymeric membranes are promising substrates for thin-film composite (TFC) membranes due to their unique interconnected pores and high porosity. However, it is still challenging to fabricate desirable electrospun substrates for organic solvent nanofiltration (OSN) owing to the relatively complex processing procedures and the organic operating environment. In this work, solvent-resistant electrospun polyimide (PI) nanofiber substrates were successfully fabricated through electrospinning followed by chemical cross-linking and heat-pressing. The cross-linking step improved the solvent tolerance of the membranes, while the heat-pressing step reduced the substrate pore size and surface roughness. However, it was found that heat-pressing at high temperatures (>140 °C) could degrade the cross-linking of PI, undermining their solvent-resistant property. A polyamide thin film layer was then synthesized on the solvent-resistant electrospun nanofibrous substrates via interfacial polymerization using reactant monomers m-phenylenediamine (MPD) and trimesoyl chloride (TMC). The TFC membranes exhibited excellent acetonitrile and acetone permeabilities of 31.28 ± 1.93 and 26.58 ± 1.13 L m−2 h−1 bar−1, respectively, with acid fuchsin (585 Da) and methyl orange (327 Da) rejections of 98.55 ± 1.24% and 92.42 ± 1.66%, respectively, in acetone. This study successfully demonstrated the potential use of electrospun PI nanofibers substrates for TFC membranes in OSN.